2014
DOI: 10.1116/1.4868615
|View full text |Cite
|
Sign up to set email alerts
|

Precision plasma etching of Si, Ge, and Ge:P by SF6 with added O2

Abstract: The impact of the O 2 content in SF 6 -O 2 gas mixtures on the etch rate and sidewall profile of silicon (Si), germanium (Ge), and phosphorous doped germanium (Ge:P) in reactive ion etching has been studied. The characteristics of etch rate and sidewall profile are greatly affected by the O 2 content. Below 50% of O 2 content, a large variation in Ge etch rates is found compared to that of Si, but for O 2 content above 50% the etch rates follow relatively the same trend. Lightly doped Ge shows the highest etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The maximum value of the silicon etching rate depends on different operation parameters, such as the design of the plasma system, working pressure, applied power and O 2 content. In a Corial 200 IL operating at a frequency of 13.56 MHz (100 W), Wongwanitwattana et al 12 obtained a maximum in Si etching rate (450 nm/min) for 5% O 2 in SF 6 / O 2 mixture and a working pressure of 2.6 Pa. D'Agostino et al 18 found a maximum in Si etching rate (about 400 nm/min) for 40% O 2 content in SF 6 /O 2 capacitively coupled plasma SO-30 (d), together with their texture line profiles taken along the diagonal of the AFM image, which are traced for the same height scale [-500 , 500 nm]. These images reveal the formation of voids and roughened surfaces with different sizes of granules ranging from 80 nm to 1 µm.…”
Section: Etching Ratementioning
confidence: 99%
See 1 more Smart Citation
“…The maximum value of the silicon etching rate depends on different operation parameters, such as the design of the plasma system, working pressure, applied power and O 2 content. In a Corial 200 IL operating at a frequency of 13.56 MHz (100 W), Wongwanitwattana et al 12 obtained a maximum in Si etching rate (450 nm/min) for 5% O 2 in SF 6 / O 2 mixture and a working pressure of 2.6 Pa. D'Agostino et al 18 found a maximum in Si etching rate (about 400 nm/min) for 40% O 2 content in SF 6 /O 2 capacitively coupled plasma SO-30 (d), together with their texture line profiles taken along the diagonal of the AFM image, which are traced for the same height scale [-500 , 500 nm]. These images reveal the formation of voids and roughened surfaces with different sizes of granules ranging from 80 nm to 1 µm.…”
Section: Etching Ratementioning
confidence: 99%
“…Etching is well-known as a consequence of plasma surface activation that results in morphological changes. SF 6 /O 2 plasma mixture, providing the highly reactive etchant fluorine atoms, is widely used for silicon surface nanostructuring, [9][10][11][12][13][14] where the resulted Si nanostructures exhibited remarkable enhanced antireflective surface and light trapping efficiency, which is of great importance for photovoltaic applications to enhance the light absorption in Si solar cells. 10,11,13 The technological motivation behind our present work is to investigate, besides the light anti-reflection property, other potential applications of the Si nanostructures using the maskless SF 6 /O 2 plasma etching, such as light emitting (photoluminescence), photo-sensing (spectral response) and humidity sensing.…”
Section: Introductionmentioning
confidence: 99%
“…3 A much faster etch rate is reported in fluorine plasma with isotropic behavior. [4][5][6][10][11][12] The etch mechanisms were reported to be quite similar to the ones of silicon, except for the inability for GeO x F y to inhibit the etching at room temperature (compared to SiO x F y that quenches the etching) 5,6 and the different sulfides stoichiometry (GeS 2 compared to SiS) and volatility (GeS 2 is less volatile than SiS). 4,13 In general, germanium etching is faster than silicon etching in fluorinebased plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…4,13 In general, germanium etching is faster than silicon etching in fluorinebased plasmas. 4 Some anisotropic etching of germanium in fluorine based plasma has been reported for SF 6 /O 2 plasma with a large concentration of oxygen 12 and in a CF 4 -based plasma in a silicon rich environment. 11 Deep silicon etching is generally performed using time multiplexed plasma etching, also-called the Bosch process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation